Agri-food manufacturing sector in Romania: Internal sizes and in the European context - Mirela-Adriana Rusali (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The sustainability of the food supply of the population in all Member States is a priority objective of the current CAP, with important implications both for ensuring food security and for developing the rural economy. In this context, the European sustainable development economic model promotes based on competitiveness, innovation and knowledge, where a key role lies with the small and medium-sized enterprise sector, due to its great flexibility in adapting the business to new market requirements. The research method used the comparison of the relevant economic and financial indicators for the activity of enterprises in the agro-food industry, in order to analyze the structure and level of development of the sector and to identify possible divergences between Romania and EU-28. The statistical material was provided mainly by Eurostat and NIS - The survey on the activity of the manufacturing enterprises data - NACE Rev.2 codes.
Keywords: L6; Q1; O5; 330; agri-food manufacturing; sustainable development; European Union